2019
DOI: 10.3390/molecules24081611
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction of Some Bioactive Compounds from Tobacco Waste

Abstract: This is the first study on ultrasound-assisted extraction (UAE) of bioactive compounds from different types of tobacco industry wastes (scrap, dust, and midrib). The obtained results were compared with starting raw material (tobacco leaves) to see the changes in bioactive compounds during tobacco processing. Results suggested that tobacco waste extracts possess antioxidant activity and considerable amounts of targeted bioactive compounds (phenolics and solanesol). The content of chlorogenic acid varied between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 38 publications
6
25
1
2
Order By: Relevance
“…19 Taj DES se pokazao dobrim otapalom za acetaminofen, komponentu s analgetičkim i antipiretičkim djelovanjem 21 kao i dobro otapalo za ekstrakciju fenolnih spojeva u lišću masline, 22 fenolnih spojeva u kori citrusa, 23 rosmarinske kiseline i rosmarinske kiselina-3'-glukozida iz obične celinščice (Prunella vulgaris L.) 24 te katehina iz zelenog čaja. 25 Također, u našim prethodnim istraživanjima, gdje su fenolne komponente ekstrahirane uz pomoć vode u subkritičnom stanju 10 ili ekstrakcijom potpomognutom ultrazvukom, 7 pokazano je da je refabrikat, kao vrsta duhanskog industrijskog otpada najbogatiji ciljanim bioaktivnim spojevima. Nakon provedenog "screeninga" na odabranom uzorku refabrikata s odabranim otapalom kolin klorid/etilen glikolom, na temelju Box-Behnkenovog plana pokusa (tablica 4) provedene su ekstrakcije tijekom kojih su mijenjani parametri ekstrakcije: vrijeme miješanja (od 30 do 90 min), temperatura miješanja (od 30 do 70 °C) te udio vode u otapalu (od 10 do 30 %).…”
Section: P2unclassified
See 1 more Smart Citation
“…19 Taj DES se pokazao dobrim otapalom za acetaminofen, komponentu s analgetičkim i antipiretičkim djelovanjem 21 kao i dobro otapalo za ekstrakciju fenolnih spojeva u lišću masline, 22 fenolnih spojeva u kori citrusa, 23 rosmarinske kiseline i rosmarinske kiselina-3'-glukozida iz obične celinščice (Prunella vulgaris L.) 24 te katehina iz zelenog čaja. 25 Također, u našim prethodnim istraživanjima, gdje su fenolne komponente ekstrahirane uz pomoć vode u subkritičnom stanju 10 ili ekstrakcijom potpomognutom ultrazvukom, 7 pokazano je da je refabrikat, kao vrsta duhanskog industrijskog otpada najbogatiji ciljanim bioaktivnim spojevima. Nakon provedenog "screeninga" na odabranom uzorku refabrikata s odabranim otapalom kolin klorid/etilen glikolom, na temelju Box-Behnkenovog plana pokusa (tablica 4) provedene su ekstrakcije tijekom kojih su mijenjani parametri ekstrakcije: vrijeme miješanja (od 30 do 90 min), temperatura miješanja (od 30 do 70 °C) te udio vode u otapalu (od 10 do 30 %).…”
Section: P2unclassified
“…Zbrinjavanje takvih vrsta otpada postaje pitanje od javnog interesa zbog njihovih potencijalnih utjecaja na okoliš i ljudsko zdravlje. 5,6 Nekoliko je istraživanja pokazalo da je duhanski otpad potencijalno primjenjiv izvor bioaktivnih spojeva, 7,8,9,10 poglavito zbog neuobičajene dominacije klorogenskih kiselina (klorogenska kiselina, neoklorogenska kiselina i kriptoklorogenska kiselina) te rutina. 11 Klorogenska kiselina i rutin su visoko-vrijedni prirodni fenolni spojevi koji se upotrebljavaju u farmaceutskoj i kemijskoj industriji, a njihova identifikacija i kvantifikacija u duhanskom otpadu također je od velike važnosti.…”
unclassified
“…Although not consumed as a food, it is partially consumed by digestive system (mouth) and its sensory properties such as aroma, flavor and odor are the most important attribute to define consumer acceptance of tobacco and tobacco products. Besides consuming by smoking, a small part of total tobacco production (less than 10%) is for consummation by chewing and sniffing [1,2]. Sensory properties of products may help to determine whether a product will be preferred over another.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Yao et al [13], it was found that solanesol protected human hepatic L02 cells from ethanol-induced oxidative injury via upregulation of haem oxygenase-1 (HO-1), an inducible enzyme with major antioxidant and anti-inflammatory functions [21], and heat shock protein 70, which plays a key cytoprotective role in protein homeostasis and participates in multiple cellular signaling events [22]. A recent study by Banožić et al [23] showed that solanesol and phenolics are the main bioactive compounds in the extracts of different types of tobacco industry wastes (scrap, dust, and midrib). Furthermore, noticeable differences in bioactive compound content and antioxidant activity are found in extracts related to ultrasound-assisted extraction conditions and type of tobacco waste.…”
Section: Bioactivities Of Solanesolmentioning
confidence: 99%